A Rare Cause of Hemifacial Spasm: Papillary Oncocytic Cystadenoma - Ozan Erol; Erdinç Aydın (Balkan Medical Journal, 2016)
Background: Hemifacial spasm is a sudden, involuntary and synchronous spasm of the facial muscles. The most frequent cause of this condition is compression of the facial nerves due to vascular pathologies. The most commonly used method of treatment is Botulinum toxin injection. However, the gold standard treatment is surgical treatment.